The United Nations and Nordic identity - Reflections on Finnish UN policy in the 2000s - Tuominen Hanna; Kronlund Anna (Finnish International Studies Association (FISA), 2025)
Support for the United Nations (UN) has been a strong priority for the Nordic states. The group has been cooperating to promote their shared values and interests since the 1960s. The Nordics have gained a reputation as do-gooders, norm advocates and strong supporters of the UN. This article studies Finland’s UN policy in the 2000s from the perspective of Nordic identity, specifically how the Finnish approach reflects the common identity within the three pillars of the UN system. On the theoretical level the article is based on the literature covering group politics and collective identity. We focus on the value-based, expressive and instrumental dimensions of Nordic identity, drawing on Finnish foreign policy documentation and interviews with key Finnish UN diplomats and policymakers. According to the findings, Nordic identity is essential for Finnish UN policy, even if there is variation in time and in policy areas.